A preliminary checklist of the Angiospermic flora of Ghagotia Union under Kapasia Upazila in Gazipur District, Bangladesh - Alam, Mohammad Shah; Hassan, Md Abul; Uddin, Mohammad Zashim (Bangladesh Journal of Plant Taxonomy, 2006)
Angiospermic flora of Ghagotia Union representing Magnoliopsida (Dicots) and Liliopsida (Monocots) have been inventoried after survey during the years of 2004 and 2005. A total of 187 species have been recorded from the area. These have been assigned to 65 families and 160 genera. Magnoliopsida is represented by 50 families, 113 genera and 133 species, whereas Liliopsida is represented by 15 families, 47 genera and 54 species. Key words: Preliminary checklist, Angiospermic flora, Ghagotia Union, Gazipur, Bangladesh DOI: 10.3329/bjpt.v13i2.586 Bangladesh J. Plant Taxon. 13(2): 155-170, 2006 (December)